PENGARUH PENERIMAAN OLEH TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR SISWA DI SMP DAN SMA MUHAMMADIYAH SE-KOTA BINJAI - Sefni Rama Putri (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2018)
This research was influented by student learning motivation which is still in low level. Acceptance by peer were external and internal factors that affect students learning motivation. This research aims to describe: (1) students’ peer acceptance, (2) students’ learning motivation, (3) influention of peer acceptance toward students’ learning motivation. This research using descriptive quantitative approach. The population were the students of grade VII and XI which numbered 442 students, samples were 179 students, which was selected by the technique of proportional random sampling. Data were analysis using descriptive statistics and simple regression. The results of this research: (1) students’ peer acceptance was on the high category, (2) students’ learning motivation was on the high category, (3) there is a influention of peer acceptance to the students’ learning motivation to 29%.